2008
DOI: 10.1371/journal.pone.0001797
|View full text |Cite
|
Sign up to set email alerts
|

The Orexigenic Effect of Ghrelin Is Mediated through Central Activation of the Endogenous Cannabinoid System

Abstract: IntroductionGhrelin and cannabinoids stimulate appetite, this effect possibly being mediated by the activation of hypothalamic AMP-activated protein kinase (AMPK), a key enzyme in appetite and metabolism regulation. The cannabinoid receptor type 1 (CB1) antagonist rimonabant can block the orexigenic effect of ghrelin. In this study, we have elucidated the mechanism of the putative ghrelin-cannabinoid interaction.MethodsThe effects of ghrelin and CB1 antagonist rimonabant in wild-type mice, and the effect of gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
284
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 278 publications
(301 citation statements)
references
References 34 publications
(51 reference statements)
8
284
0
9
Order By: Relevance
“…Hypothalamic AMPK has also been suggested as the mediator of the orexigenic effects of several other metabolic hormones and neuropeptides/modulators including cannabinoids (Kola et al, 2005) and glucocorticoids (Christ-Crain et al, 2008). Evidence that AMPK activity in the hypothalamus is also regulated by anorexigenic hormones: leptin (Andersson et al, 2004;Minokoshi et al, 2004) and insulin (Minokoshi et al, 2004), further demonstrates that hypothalamic AMPK is directly involved in appetite regulation.…”
Section: Both Havementioning
confidence: 99%
See 2 more Smart Citations
“…Hypothalamic AMPK has also been suggested as the mediator of the orexigenic effects of several other metabolic hormones and neuropeptides/modulators including cannabinoids (Kola et al, 2005) and glucocorticoids (Christ-Crain et al, 2008). Evidence that AMPK activity in the hypothalamus is also regulated by anorexigenic hormones: leptin (Andersson et al, 2004;Minokoshi et al, 2004) and insulin (Minokoshi et al, 2004), further demonstrates that hypothalamic AMPK is directly involved in appetite regulation.…”
Section: Both Havementioning
confidence: 99%
“…We have shown that rat and mouse hypothalamic AMPK activity is stimulated by both central (intracerebroventricular) and peripheral (intraperitoneal) ghrelin administration (Kola et al, 2005;Kola et al, 2008). The central orexigenic effect of ghrelin is AMPK-dependent as compound C, an inhibitor of AMPK, completely prevented ghrelin's orexigenic effect, and adenoviruses harbouring α1/α2 dominant negative AMPK were able to impair the stimulatory effect of ghrelin on food intake (Lopez et al, 2008).…”
Section: Both Havementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such a mechanism has been shown to be responsible for (1) the disinhibition of the release of the orexigenic neuropeptide, a melanin-concentrating hormone (MCH), from LH neurons through a retrograde inhibition of g-aminobutyric acid (GABA) release; 9 and (2) the inhibition of anorectic neurons in the PVN after a sequential activation of either ghrelin or 'fast' glucocorticoid receptors in these neurons (which likely produce the corticotropin-releasing hormone (CRH)), the biosynthesis and release of ECs, and subsequent retrograde CB 1 -mediated inhibition of glutamate release from parvocellular neurons innervating these neurons. 10,11 In some cases, 9,10 these retrograde orexigenic actions of ECs are under the negative control of post-synaptic leptin receptors that reduce EC biosynthesis by decreasing intracellular calcium. In fact, it had been shown earlier that hypothalamic EC levels are inhibited by an intravenous injection of leptin in rats, an effect that is likely responsible for the permanently elevated EC levels in the hypothalamus of obese rodents that lack leptin (ob/ob mice) or fully functional leptin receptors (db/db mice and fa/fa Zucker rats).…”
Section: Brief Introduction To the Endocannabinoid Systemmentioning
confidence: 99%
“…It has been demonstrated that administration of ghrelin to rats affects AMPK activity, although this effect is tissue-specific. In the hypothalamus, central and peripheral ghrelin treatments enhance protein levels of AMPK and this activation and alterations on lipid metabolism mediate the Page 17 of 37 A c c e p t e d M a n u s c r i p t 17 orexigenic effects of ghrelin (Andersson et al 2004;Kohno et al 2008;Kola et al 2005Kola et al , 2008Lopez et al 2008). In fed animals peripheral chronic and acute ghrelin treatments provoked AMPK activation in the heart, while in liver and adipose tissue it was inhibited and no effect was detected on skeletal muscle (Barazzoni et al 2005;Kola et al 2005).…”
mentioning
confidence: 99%